2011
DOI: 10.2105/ajph.2010.300099
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Workplace Exposures in Vietnamese Women Working in California Nail Salons

Abstract: Using a CBPR approach that engaged community members in the research process contributed to the successful recruitment of salon workers. Measured levels of toluene, methyl methacrylate, and total volatile organic compounds were higher than recommended guidelines to prevent health symptoms such as headaches, irritations, and breathing problems, which were frequently reported in this workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
82
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 8 publications
10
82
2
Order By: Relevance
“…Nevertheless, median airborne levels of all the investigated VOC were far below the TLVs obligatory in Poland and none of the 109 nail salons enrolled in our study was seen to exceed the Polish TLV for any of the measured chemicals. It has to be, however, stated that even though the median and maximum values of total amount of airborne VOC found in our study (17.1 mg/m 3 and 139.4 mg/m 3 , respectively) were consistent with those reported in a recent study by Goldin et al (11 mg/m 3 and 87 mg/m 3 , respectively) (44), the direct comparison of airborne levels of individual VOC in nail salons among different studies is difficult, mainly due to a huge degree of variability of published data and different measures of centrality used by various authors (arithmetic/geometric means, median) (31,32,(41)(42)(43). Either way, median and maximum airborne levels of acetone, 2-butanone, isopropyl alcohol, hexamethyld- Figure 1.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nevertheless, median airborne levels of all the investigated VOC were far below the TLVs obligatory in Poland and none of the 109 nail salons enrolled in our study was seen to exceed the Polish TLV for any of the measured chemicals. It has to be, however, stated that even though the median and maximum values of total amount of airborne VOC found in our study (17.1 mg/m 3 and 139.4 mg/m 3 , respectively) were consistent with those reported in a recent study by Goldin et al (11 mg/m 3 and 87 mg/m 3 , respectively) (44), the direct comparison of airborne levels of individual VOC in nail salons among different studies is difficult, mainly due to a huge degree of variability of published data and different measures of centrality used by various authors (arithmetic/geometric means, median) (31,32,(41)(42)(43). Either way, median and maximum airborne levels of acetone, 2-butanone, isopropyl alcohol, hexamethyld- Figure 1.…”
Section: Discussionsupporting
confidence: 88%
“…The VOC most frequently detected in nail salon air samples were acetone, ethanol, toluene, 2-propanol, 2-butanone, ethyl acetate and n-butyl acetate (all of them in >90% of all samples), in contrast to EMA and MMA, which were found in only 51% and 18% of analyzed air samples, respectively. Similar low frequencies of EMA, MMA or both were reported by the majority of previous studies even though the subjects involved in these studies reported an almost exclusive employment of the EMA/MMA-involving techniques of artificial nail sculpturing during their work time (31,32,(41)(42)(43). It is thus possible that besides techniques employed, other factors (such as ventilation, EMA/MMA content in used nail products, etc) not involved in any of these studies, may influence the resultant relative airborne levels of EMA or MMA.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A study of air in Californian salons revealed that measured values of isopropyl alcohol and ethyl acetate were within the California Division of Occupational Safety and Health's occupational limits. However, the average measured value of toluene from personal air monitoring was greater than the 0.08 ppm, which is recommended by the California Environmental Protection Agency [82]. Although MMA is banned, the average level of MMA was measured at 0.54 ppm, which is several times higher than the recommended 0.17 ppm.…”
Section: Occupational Exposurementioning
confidence: 76%
“…The use of pure methyl methacrylate compounds has been largely discontinued due to legislation restricting its usage [35]. Regardless, MMA has been sampled in the ambient air of nail salons, which suggests that its usage continues [82]. In addition, the use of other methacrylate monomers is still allowed.…”
Section: Discussionmentioning
confidence: 99%